KUALITAS HIDUP BERDASARKAN KARAKTERISTIK PASIEN PASCA STROKE (Studi di RSUD Tugurejo Kota Semarang) - Ulfa Bariroh; Henry Setyawan Susanto; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2016)
Stroke is the leading cause of functional disorder that can affect the patient's life in various aspects (physical, emotional, psychological, cognitive, and social). The level of physical and mental disability in patients with post-stroke can affect the quality of life of patients. In this study aims to describe the post-stroke patient quality of life based on the characteristics. This is a descriptive study with cross-sectional approach. The instrument used in this study was a questionnaire. The sample is 100, by using simple random sampling technique. This research uses descriptive data analysis results showed that the poor quality of life more in respondents older than 55 years (67.7%), male sex (52.1%), did not attend school (100%), not work (58.5%), had income below the minimum wage (56.6%), not having a partner (78.8%) and various non-hemorrhagic stroke (52.6%). post-stroke patients are advised to read a lot about stroke and stroke a lot to find out about other than that for post-stroke patients who have a spouse is expected to continue to provide support.